The effect of limited search ability on the quality of competitive rent-seeking clubs - Shmuel Nitzan; Kobi Kriesler (Bar-Ilan University, Department of Economics, 2010)
A competitive rent-seeking club (CRSC) offers its members the chance of winning a prize (status, position, privilege) by being selected, typically, by a civil servant or a politician. The selector replaces in our setting the usual contest success function; instead of determining the winner on the basis of the club-members' efforts, he selects the winner on the basis of quality. This paper focuses on the effect of incomplete search of the selector on the efficiency of democratic self-governing and decentralized RSC's that control admittance to the club and its transparency, assuming that quality of their members is fixed. The incomplete search of the selector is assumed to take the simple form of fixed random sampling of the contestants - the members of the CRSC. Our results imply that, even when active rent-seeking expenditures are disregarded, the decisions of CRSC's regarding their composition and transparency tend to reduce quality and are therefore inefficient.
Keywords: D70; D71; D72; 330; competitive rent-seeking clubs; self governance; decentralized decisions; quality competition; selection by fixed random sampling; simple majority rule; endogenous membership determination; transparency; inefficiency; quality decay; Rent-Seeking; Neue politische Ökonomie; Theorie